Ethnobotanical survey of plants used as traditional herbs and spices in north-eastern Namibia - Tomas, Abner; Cheikhyoussef, Ahmad; Chinsembu, Kazhila; Maroyi, Alfred (Ethnobotany Research and Applications, 2026)
Background: Research on indigenous knowledge as an alternative key to unlock the power of health benefits associated with plant species has gained much interest recently. However, there is a lack of documented information about the use of indigenous plants as traditional herbs and spices and their contributions to health benefits in north-eastern Namibia. The aim of this study was to conduct an ethnobotanical survey of indigenous knowledge of plants used as culinary herbs and spices in north-eastern Namibia. Methods: Using semi-structured interviews and closed-end questionnaires, ethnobotanical data was collected from random selected informants in the Kabbe North and Kabbe South constituencies between December 2018 and April 2019 without following a specific order. Plant parts and photographs of each species mentioned by at least three independent participants were collected and taken for further identification. Results: Twenty-three (23) plant species belonging to 16 plant families were collected. Furthermore, the largest proportion of plants used as traditional herbs and spices documented belonged to the family Malvaceae. Leaves were the most used part in food preparations, mainly as leafy vegetables, seasoning, preservation, flavouring, and traditional medicines, followed by roots. Conclusions: Our preliminary results will serve as a reference, which documents and preserves the indigenous knowledge of plants used as culinary herbs and spices in Kabbe constituencies, Zambezi region, Namibia. Further studies may be needed to determine the biological activities, chemical compounds, and toxicity to support the safe usage of these plants as food additives and natural preservatives for food safety applications. Keywords: Ethnobotanical survey, herbs, indigenous knowledge, spices, Zambezi region.